How democratic decentralisation facilitates, sustains, and interrupts market-driven development in India. Issue 3 (3rd April 2019) - Daftary, Dolly
ABSTRACT: Democratic decentralisation has emerged as an instrument to implement market-driven development, and elected bodies now extend commercial inputs for commodity production and link households to firms. However, the nature of market-driven development under this condition is understudied. This article focuses on an Indian case where, while access to market inputs was shaped by political capital with elected leaders, narrowing market participation, leaders – now market intermediaries – fostered trust in firms, helping sustain market participation. Conflicts over electoral politics interrupted market production. Markets rely on state institutions and are intertwined with politics, contrary to market proponents' claims that markets stand above society and are unmediated spaces of exchange.